Reliability and validity of the loughborough soccer passing test in adolescent males: implications for talent identification - McDermott, G.; Burnett, A. F.; Robertson, S. J.; Chia, M.; Jenkins, D. (International Journal of Sports Science and Coaching, 2015)
This study examined measurement properties of the Loughborough Soccer Passing Test (LSPT) in two groups of Under 13 players (a competitive group and a recreational group; n=26 in each) and a group of competitive Under 19 players (n=25). Participants completed the LSPT twice on a single day then repeated the protocol one week later. Significant differences between the three groups were evident for execution time and total time, with better players achieving superior scores. Hence, the test showed discriminant validity. A significant familiarisation effect for penalty time was also shown from Day 1 - Trial 1 to Day 2 - Trial 2 in the Under 13-Recreational group. The Under 19 - Competitive group showed the greatest number of acceptable (>0.70) ICC values for within-day and between-day reliability of the LSPT while the Under 13 - Recreational group showed less than acceptable reliability values. These findings have implications for talent identification and development programs.